2021
DOI: 10.1080/13685538.2021.1920912
|View full text |Cite
|
Sign up to set email alerts
|

Low free testosterone level as a predictor of cardiovascular events in Japanese men with coronary risk factors

Abstract: Aim: We investigated whether low plasma free testosterone (FT) levels could predict cardiovascular events (CVE) in Japanese men with coronary risk factors. Methods: Male patients with classical coronary risk factors who had undergone serum FT testing were enrolled. New incidences of CVE were retrospectively investigated among all eligible participants based on their medical records. Results: Overall, 466 male outpatients with coronary risk factors without a previous history of CVE were identified. Throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…BMI and waist circumference were negatively correlated with testosterone levels, although BMI was not associated with low testosterone levels in this study 24 . Some Japanese studies have found no association between BMI and low‐testosterone, similar to this study 9 . The prevalence of obesity and overweight in Japanese adults is rather low in international comparisons 25 and could explain why BMI was not a significant factor in this study.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…BMI and waist circumference were negatively correlated with testosterone levels, although BMI was not associated with low testosterone levels in this study 24 . Some Japanese studies have found no association between BMI and low‐testosterone, similar to this study 9 . The prevalence of obesity and overweight in Japanese adults is rather low in international comparisons 25 and could explain why BMI was not a significant factor in this study.…”
Section: Discussionsupporting
confidence: 63%
“…24 Some Japanese studies have found no association between BMI and low-testosterone, similar to this study. 9 The prevalence of obesity and overweight in Japanese adults is rather low in international comparisons 25 and could explain why BMI was not a significant factor in this study.…”
Section: Sports Club Activity In Childhood Maymentioning
confidence: 66%
See 2 more Smart Citations
“…Testosterone levels decrease with age, low serum testosterone levels are linked to premature coronary artery disease (CAD) and with increased risk of cardiovascular (CV) mortality. Reduced levels of testosterone are also a risk factor for type 2 diabetes (T2D), inflammation, dyslipidemia and metabolic syndrome (MS) [ [1] , [2] , [3] , [4] , [5] ]. A systematic meta-analysis enrolled 3467 male patients with T2DM (1079 patients with a low testosterone level versus 2388 patients with a normal testosterone level) and investigated the association between testosterone level and cardiovascular risk in male patients with type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%